2022
DOI: 10.3233/wor-205340
|View full text |Cite
|
Sign up to set email alerts
|

Effects of worksite exercise intervention (PRODET®) on well-being at work and capability in performing work-related sedentary tasks: A pilot study

Abstract: BACKGROUND: Companies have tried to carry out interventions in order to mitigate the risks associated with losses in productivity and the health of employees. OBJECTIVE: This intervention trial evaluated the effect of a supervised exercise intervention based on aerobic capacity and strength on well-being at work and capability in performing work tasks. METHODOLOGY: The sample was composed of 67 participants (N = 67, mean age 34.31 years) and investigated a 12-week group physical exercise program in the workpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Interestingly, those studies reported both perceived improvements for example, in pain scales 36 , 37 and objective improvements for example, in postural angles 37 or days of sick leave. 38 Furthermore, not only pain but also psychosocial dimensions as QoL 36 , 39 and job satisfaction 19 , 40 were affected. Especially job satisfaction seems to be positively influenced by physical activity 41 and physical activity-related interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, those studies reported both perceived improvements for example, in pain scales 36 , 37 and objective improvements for example, in postural angles 37 or days of sick leave. 38 Furthermore, not only pain but also psychosocial dimensions as QoL 36 , 39 and job satisfaction 19 , 40 were affected. Especially job satisfaction seems to be positively influenced by physical activity 41 and physical activity-related interventions.…”
Section: Discussionmentioning
confidence: 99%